Brands, geographical origin, and the global economy : a history from the nineteenth century to the present - Higgins, David M. (Cambridge, United Kingdom ; New York, NY, USA : Cambridge University Press, 2018)
'This book had its genesis in the mid-1990s when I began researching the trademarks used by Sheffield cutlers and the emergence of'Sheffield'. Subsequently, collaboration with Geoff Tweedale, Mads Mordhorst and Dev Gangjee, and participation in conferences and workshops, extended my interest in IGOs. Over time, I realised that this subject had been comparatively neglected by business historians. There were, of course, exceptions. Paul Duguid, for example, is prominent in debates on how and why regulatory and institutional change affected the development of IGOs in the port industry during the nineteenth and early twentieth centuries. Nonetheless, it is fair to say that research on these indications has been dominated by scholars in legal history, marketing, and agricultural-rural development'--
Geographical Origin in the Global Economy -- Firms and Indications of Geographical Origin in the First Global Economy -- Country of Origin and Agricultural Trade during the Nineteenth Century -- Cooperation, Country of Origin, and Agricultural Trade during the Interwar Period --'Unfair Competition' and the British Merchandise Marks Act, 1926 -- From Paris to London : The International Legal Framework for the Protection of IGOs, ca. 1880-1945 -- The Evolving International Framework for the Protection of IGOs after 1945 -- EU Policy on Geographical Indications : Ambitious, but Misguided? --'Made in' and Country of Origin in the Post-1945 Period -- Reflections on the History of IGOs.
Includes bibliographical references (pages 296-325) and index.
Keywords: Marks of origin -- Law and legislation -- History; Trademarks -- Law and legislation -- History; Names, Geographical -- Law and legislation -- History